Analysis of V-Ki-Ras2 Kirsten rat sarcoma viral oncogene (Kras) and differential expressed miRNA in various stages of colorectal cancer - Lye, Kwan Liang (2013)
Colorectal cancer is one of the most prevalent cancers in Malaysia. There are many factors that contribute towards colorectal carcinogenesis and one of them is genetic predisposition. Mutations in the V-Ki-Ras2 (Kras) oncogene have been implicated in 30-50% of the colorectal cancer patients and usually lead to significantly poorer prognosis. Early detection of colorectal cancer still poses a huge problem to the clinicians as there are few or no signs at all during the initial phase of colorectal cancer. However, recently a group of small, non-coding RNAs called microRNAs (miRNAs) was discovered to play a role in colorectal carcinogenesis. Therefore, the aim for this study is to elucidate and investigate the Kras oncogene and miRNAs expression level in various stages of colorectal cancer for better understanding of this disease. In this study, colorectal cancer and adjacent normal tissue samples were obtained from Hospital Kuala Lumpur. The study was divided into 2 parts. The first part was Kras mutational studies using PCR-RFLP method and the second part was next-generation sequencing and differential expression analysis on paired cancer and normal samples. The results obtained showed that Kras mutation was at 39%. From the sequencing results, approximately 92% clean reads were obtained and length distribution showed that the small RNA ranges from 20-28 nucleotides. This study also managed to identify 22 differentially expressed miRNAs and 5 of them were chosen for further validation using real-time PCR. Three of the miRNAs that were up-regulated are miR-106a, miR-135b and miR-21, while miR-1 and miR-504 were down-regulated. Further evaluation using in silico analysis managed to identify putative targets for the miRNAs. Among the interesting findings was miR-135b targets APC gene that is involved in the Wnt signalling pathway, which is among the crucial pathways during initiation of colorectal carcinogenesis. Besides, miR-1, miR-106a and miR-21 were predicted to regulate genes involved in EGFR and Kras signalling pathways. Meanwhile, one of the putative targets for miR-504 was BCL2 gene which regulates the p53 tumor suppressor gene. Although this is only a preliminary profiling study, the results obtained can provide some insights on the role of Kras oncogene and miRNAs on colorectal carcinogenesis.